2018
DOI: 10.1002/j.2334-5837.2018.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of A3 architectural overviews in Lean Product Development Teams; A case study in the Subsea Industry

Abstract: This paper presents a case study investigating the use of A3 Architectural Overviews (A3AOs) in lean product development teams. A3AOs is a tool used in product development and lean manufacturing to increase communication and knowledge sharing across the organization. We studied the implementation in an engineering department of a global oil and gas supplier, by performing a case study and extensive depth interviews. We also studied earlier implementation initiatives of A3s in a thorough literature review. A fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…To develop completely new systems (instead of capturing an existing system architecture/knowledge). Earlier initiatives of A3AOs has found clear benefits of A3AOs but it was rarely used today (Løndal & Flak, 2018). By providing this A3AO template and approach not only the approach is applied and evaluated in a short-term research session, after one year the approach is fully embraced and incorporated in the current way of working.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop completely new systems (instead of capturing an existing system architecture/knowledge). Earlier initiatives of A3AOs has found clear benefits of A3AOs but it was rarely used today (Løndal & Flak, 2018). By providing this A3AO template and approach not only the approach is applied and evaluated in a short-term research session, after one year the approach is fully embraced and incorporated in the current way of working.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that A3AOs are considered as a good tool to communicate and capture the system architecture (Løndal & Flak, 2018). By using the A3AO most import aspects of the system (architecture) can easily be shared and consumed among stakeholders.…”
Section: Literaturementioning
confidence: 99%
“…(Borches 2010) developed A3AOs for systems architecting, but it was stated that the findings also could be implemented to fit other purposes (Borches 2010). (Viken & Muller 2018, Løndal & Falk 2018, Wiulsrød, Muller & Pennotti 2011 found the principles of A3AOs to facilitate communication and knowledge sharing.…”
Section: Lean Thinking (Lt)mentioning
confidence: 99%
“…Most A3 focused research papers includes one or more of these elements. (Viken & Muller 2018) included title, author and date, (Løndal & Falk 2018) included title and author, (Svendsen & Haskins 2016) included title, date and author, (Borches 2010) included title and author, (Singh & Muller 2013) included title, author, revision and date. We considered to include author contact information, but decided against it, as the author almost always will be part of the project organization and have his contact information presented in the project organization block.…”
Section: Mediummentioning
confidence: 99%
See 1 more Smart Citation